Pengamanan Data File Teks (Word) Menggunakan Algoritma RC4 - Dedy Ronald Saragi; Janter Manuel Gultom; Jose Andreas Tampubolon; Indra Gunawan (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
Data security on computers can provide a protection for our data. Cryptographic techniques are very important techniques in securing data. Cryptography is the science of encryption techniques where the "original text" (plaintext) is encrypted using an encryption key into "random text that is difficult to read" (ciphertext) by someone who does not have a decryption key, one of the modern cryptographic methods developed is the RC4 algorithm. RC4 algorithm (Ron’s Code / Rivest’s Cipher) is one algorithm that can be used to encrypt data so that the original data can only be read by someone who has the encryption key.